BEHAVIORAL FINANCE FACTORS AND THEIR IMPACT ON RETIREMENT CONFIDENCE AMONG MALAYSIAN OIL AND GAS SKILLED EMPLOYEES - SHABOR RAMELI, ROZILAH (2021)
Malaysia’s oil and gas (O&G) industry is not without its challenges, such as the problem of long-term oil price declining, delays, and cancellations of major projects that have resulted in a reduction in available work in the global industry, including in Malaysia. Ultimately, employee layoffs in the oil and gas industry can be anticipated due to the fall in oil prices. As a result, the problem of job security has occurred among O&G employees. However, employees’ retrenchment tends to be the last option for employers’ decisions to minimize the cost since rehiring can also be very costly. Hence, preparation for retirement is also an urgent matter that the O&G employees need to view since job insecurity issues had affected them. Although the need for individuals to increase retirement savings has been widely promoted, however, to date, limited studies are investigating causal relationships between behavioral finance factors towards savings intention and retirement confidence.